Handlebar herniation: a case of near missed abdominal injury. - Chew, K S; Amin, N M N Nik (2009)
Timely identification of specific injuries in a polytrauma case is of paramount importance in order to reduce morbidity and mortality. Unfortunately, some of these injuries are subtle and can be missed on initial primary and secondary assessments. In this paper, we report one such injury in a case of a 16-year old motorcyclist who complained of abdominal pain over the right lumbar region after the motorcycle handlebar hit his abdomen. Although initial assessment was uneventful, he was subsequently diagnosed to have a traumatic abdominal wall herniation on abdominal computed tomography after more than 24 hours of observation in the ward.